Efficiency of blast walls for protection of soft targets - Cekerevac, Damjan (2019)
The recent trend of terrorist attacks on civilian targets, including transportation systems, resulted in efforts to harden and strengthen these objects which previously were not designed to cope with this kind of threat. The blast mitigation strategies traditionally used in industrial facilities may provide an additional safety. One such solution is a blast wall that could be used for façade systems or for protection of muster areas and evacuation routes of metro and train stations or airports. This paper deals with the assessment of the blast response of protection walls. The typical types of blast walls commonly used in practice in industrial sector are described. The behavior of blast walls is characterized using simple analytical approach and finite element modelling. The advantages and limitations related to each of these characterization techniques are discussed compared with findings of other authors. Furthermore, a parametric study is performed through extrapolation of numerical models. Two common types of panels with both fixed and pinned boundary conditions are subjected to directly defined pr essure loads. Their responses are compared in order to evaluate the effects on the primary steelwork. Possible benefits deriving from typological and geometrical modifications of the local element are also presented. Particular emphasis is given to the importance of the estimation of the reaction forces, displacements and energy dissipation.